Răspuns :
daca x ∈ ( 3 , +∞) atunci x >3 ; x -3 >0 pozitiv , cond. de exponentiala
y∈ ( 3 , +∞) y-3 > ; y-3 >0 functia f(t) = ln t este monton cres.
atunci ln( y- 3) >0
--------------------- ⇒
ln( y-3 )
(x -3 ) >0 / +3
ln( y -3 )
( x -3) + 3 >3
x× y >3 ⇒ x×y ∈ (3 , +∞) parte stabila a lui R
comutativ.
ln( y-3) ln( x -3)
( x-3 ) +3 = ( y -3 ) +3
ln(y-3) ln( x -3)
( x-3 ) = ( y-3) logaritmam
ln( y-3) ln( x -3)
ln ( x-3) = ln( y-3) propr.log
ln( y-3)·ln( x -3) = ln( x-3 ) · ln ( y -3 ) adev. ,lege comutativa
y∈ ( 3 , +∞) y-3 > ; y-3 >0 functia f(t) = ln t este monton cres.
atunci ln( y- 3) >0
--------------------- ⇒
ln( y-3 )
(x -3 ) >0 / +3
ln( y -3 )
( x -3) + 3 >3
x× y >3 ⇒ x×y ∈ (3 , +∞) parte stabila a lui R
comutativ.
ln( y-3) ln( x -3)
( x-3 ) +3 = ( y -3 ) +3
ln(y-3) ln( x -3)
( x-3 ) = ( y-3) logaritmam
ln( y-3) ln( x -3)
ln ( x-3) = ln( y-3) propr.log
ln( y-3)·ln( x -3) = ln( x-3 ) · ln ( y -3 ) adev. ,lege comutativa